STRUKTUR BIAYA DAN PROFITABILITAS USAHA MINIPLANT RAJUNGAN (Portunus pelagicus) - Roslindah Daeng Siang; Nurdiana Azis (Program Studi Agrobisnis Perikanan, Fakultas Perikanan dan Ilmu Kelautan, UHO, 2015)
This study aims to determine the needs of business investment, the cost structure, cost efficiency, and profitability of the business. Collecting data using interview techniques to the owner miniplant crab (Portunus pelagicus) is a group in the village Bahari Manage Lapulu Abeli District of Kendari. Data was analyzed using quantitative and qualitative methods. The analytical tool used is investment analysis, cost analysis, defresiasi analysis, and break-even point. Results of the analysis showed that the total investment needs of businesses miniplant crab is Rp15.770.000. The ratio of return on investment of 0.23 years shows that the investments made can be returned for ± 3 months. Rajungan miniplant business cost structure is dominated by the cost of procurement of raw materials rajungan by 90%, the remaining 10% for payment of taxes, home care production, depreciation, wages, consumption, plastic bags, charcoal and salt. The use of business costs miniplant rajungan already efficient with R / C of 1.35, B / C ratio of 0.35, BEP (unit) of 92 kg and BEP (price) of Rp10.580.650. Profitability of business or level of ability of businesses generate profits of 0.35, meaning any business investment miniplant Rp1 crab will yield a profit of Rp0.35Keyword : Cost, business profitability, investation, rajungan miniplant